2014
DOI: 10.1039/c3cc47601d
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared photolysis of a Ru polypyridyl complex by upconverting nanoparticles

Abstract: NaYF4:Yb(3+)/Er(3+)nanocrystals upconvert near infrared light (980 nm) into higher energy visible photons capable of effecting the photodissociation of the monodentate pyridyl ligand in cis-[Ru(bpy)2(py)2]Cl2: opening an opportunity for advancing the use of photoactivatable metal complexes in medicine and biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 23 publications
0
51
0
Order By: Relevance
“…However, a new approach that is currently gaining momentum may help overcome this problem: the use in photochemotherapy of compounds and materials designed to upconvert near-infrared light into higher-energy visible photons. It has been applied to activation of ruthenium complexes suggested as prodrugs for photoactivatable anticancer therapy (59,60). Perhaps, the same or similar compounds could help trigger the azobenzene photoisomerization in lipid amphiphiles by infrared light.…”
Section: Phototriggerable Flipidsmentioning
confidence: 99%
“…However, a new approach that is currently gaining momentum may help overcome this problem: the use in photochemotherapy of compounds and materials designed to upconvert near-infrared light into higher-energy visible photons. It has been applied to activation of ruthenium complexes suggested as prodrugs for photoactivatable anticancer therapy (59,60). Perhaps, the same or similar compounds could help trigger the azobenzene photoisomerization in lipid amphiphiles by infrared light.…”
Section: Phototriggerable Flipidsmentioning
confidence: 99%
“…[29,30] Previous systems have successfully used ruthenium compounds, often coupled with upconverting nanoparticles, to achieve near-IR activation of the ruthenium and release of active protein. [31,32] …”
mentioning
confidence: 99%
“…Ford and co-workers showedt hat the NIR irradiation of UCNPs loaded with either the Roussin black salt anion or the photoactivated CO-releasing moiety (photoCORM) trans-[Mn(2,2'-bipyridine)(PPh 3 ) 2 (CO) 2 ] results in the release of NO and CO, respectively. [13,14] Similarly, we have demonstrated that related upconversion nanosystems promoted the release of pyridine fromaR u-polypyridyl complex [16] and the generation of aP t II speciesf rom aP t IV prodrug candidate. [17] Alternatively,H ee tal.…”
Section: Introductionmentioning
confidence: 92%